Online Informal Learning of English Activities to Improve Students’ English Communication Skills - Zahrotul Lutfiana; Diah Kristina; Sumardi Sumardi (STAI Hubbulwathan Duri, 2021)
This study aims to learn about students' experiences developing their speaking skills using Online Informal Learning of English (OILE) activities. The researcher gathered data for this narrative study by interviewing and observing three English education students at a State University in Central Java. The data were then evaluated qualitatively. The results indicated that students learned several aspects of speaking and communicating in English using Youtube video content, including pronunciation, intonation, and expressiveness. Additionally, the students used a variety of social media and chat platforms to engage with their international peers in English. Additionally, students favoured this informal learning mechanism because they recognized the efficacy of these online everyday learning activities in pleasantly achieving meaningful learning goals. Additionally, OILE activities aided students' speaking performance during informal learning activities.